Making Worlds in a Waking Dream: Where Bion Intersects Friston on the Shaping and Breaking of Psychic Reality - Mellor, Matthew John (Frontiers in Psychology, 2018)
With the publication of Wilfred Bion’s text 'Learning from Experience', psychoanalysis was afforded a new schema for understanding the processes and implications involved in an infant’s contact with their caregivers. As a result, our conception of some of the most fundamental phenomena of psychic life was significantly enriched. By proposing his theory of alpha-functioning, Bion mapped out how meaningful connections to the internal and external worlds become established in the mind. In contrast, and through working clinically with psychotic patients, Bion revealed how these ties can catastrophically come undone. It is with these ideas, as well as their links to a corresponding set of neuroscientific constructs relating to the Markov blanket and principally developed by Karl Friston, that this paper is concerned. Through an investigation of the psychic functioning originally dubbed ‘dream-work-alpha’, the paper’s first section focuses on how Bion conceived of the creation of a ‘contact-barrier’ that allows for the differentiation of consciousness from an unconscious mind. Casting the ramifications of this organisation in sharp relief, the psychotic disorganisation of the contact-barrier is then explored. The discussion subsequently broadens to incorporate contemporary theories from free energy neuroscience that bear significant and illuminating relations to the psychoanalytic ideas espoused by Bion over half a century ago. Finally, through posing a series of three questions with accompanying discussions, a superimposition of these theoretical schemas is attempted. These suggestions directly address 1. whether there is an intimate connection between the interoceptive contact-barrier and the exteroceptive Markov blanket, 2. whether a disobjectalising of the contact-barrier may be reflected as a tear in the functional fabric of the Markov blanket, and 3. what the clinical implications are of working at the level of the projected surface. Ultimately, the aim of the paper is to expose relevant points of contact within and between the varying conceptual frameworks; frameworks that ultimately derive from disciplines that are both concerned with examining the underlying mechanisms of the mind-brain.